Innowacje w usługach komunalnych na przykładzie gmin województwa świętokrzyskiego - Stachowicz, Monika (Innovations in Local Services on the Example of Gminas of Świętokrzyskie Voivodeship, 2008)
The concept of innovations has been known since the 1960s of the 20th century. However, it is presently becoming the subject of many considerations and discussions. The article presents examples of innovations in local services in gminas of świętokrzyskie voivodship. They depend mostly on the expansion of infrastructure, development of services, and intercommunal co-operation. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 136-143